Materielle Minder: Om at huske med genstand og krop - Makovicy, Nicolette (Tidsskriftet Antropologi, 2005)
Nicolette Makovicy: Material Memories: On Remembering with Object and Body We live surrounded by cultural objects, either of our own making, or appropriated from other sources through purchase or gift. This article is an exploration of how our interaction with material culture can affect how we remember, and inquires into the wider implications this has on knowledge and memories which circulate in social relations and across generations. The specific object of study is handmade bobbin lace, its production and circulation in the central Slovak provincial town of Banská Bystrica and its surrounding villages. The author takes a critical stance towards the conventional notion that objects can act as analogues for memory, as illustrated by Aristotle’s memoria. Instead, the author attempts to explore what an approach which underscores memory as a spontaneous recall. The article first deals with the relationship between skill, an embodied form of knowledge which relies on the physical training of the body to perform precise movements, and the product of this knowledge, the lace, as a means of transferring craft knowledge between makers. It is argued that the body and the senses are indispensable to this transfer, the key to the understanding and memorization of knowledge being physical reproduction. The second part of the article deals with lace articles as an element of household décor. It is shown that lace articles, while all being spoken of as making permanent memories through their materiality, most often have shifting meanings attached to them determined by a frequent circulation between households. Finally, it is suggested that the emphasis on materiality is used by the informants as a discursive device in their attempts to ground themselves socially and historically.